The Role Of Workload And Work Motivation In Influencing Performance Through Job Satisfaction - I Nyoman Swedana (Jurnal Manajemen, 2023)
Job satisfaction is quite an exciting and essential issue because it has greatly benefited the interests of the individual, the company, and the existing community. This study aims to analyze the performance of nurses who are influenced by workload and motivation through job satisfaction. This research was conducted on nurses at Undata Hospital, Palu, where 152 were used as respondents. Data collection techniques used questionnaires with Likert scale measurements and interval scales. The analytical method used is Partial Least Square (PLS) using WarpPLS 7.0 software. The results of this study indicate that motivation has a positive and significant effect on nurse performance. At the same time, the workload does not affect performance. Satisfaction does not affect performance. These results are expected to be considered by related parties in maintaining nurse performance.